Design Of High Speed and High Secure Fully Elgamal (F.E) Encryption And Decryption System - et. al, Puttamraju Padma Mounika (International Journal of Advanced Science and Technology, 2020)
The demand for security of digital data and handling of algorithms for more complex structures has risen exponentially from last decades. There was a problem occurred when publicly computing with private data or modification of functions or algorithms. To overcome this problem, it is required to perform computations on encrypted data by computer. Here Implementing feasible large integer multiplication hardware is critical to accelerate the FHE evaluation process. Hence in this paper, design a high speed and high secure fully elgamal based homomorphic encryption and decryption system. Fully Elgamal Encryption and decryption (FEED) system allows computations to be carried out directly on cipher texts for ensuring data privacy on untrusted servers, thus attracting much attention for cloud computing applications. From the simulation results, observing that proposed system gives effective output.